The geographical location of manufacturing exporters in South Africa - Wim Naudé; Marianne Matthee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper provides empirical evidence on the location of export-oriented manufacturing firms in Africa (South Africa), and on how the patterns of location has changed over the past decade after the country embarked on trade liberalization. It is found that (a) the proximity to a port is an important consideration in most export-oriented manufacturing firms' location, with more than 70 per cent of manufacturing exports in South Africa originating from a band of 100 km from a port; and (b) there is a second band of location of these firms at a distance of between 200 and 400 km from the port. Between 1996 and 2004, manufactured exports in the band between 200 and 400 km from the nearest port increased. Various possible explanations for this dispersion of export location are discussed. These include (a) changes in international and domestic transport costs; (b) an increase in manufactured exports that depend on natural resources due to demand factors; and/or (c) inflation in land-rents or wage rates in the vicinity of hubs; and/or (d) the increasing productivity of export plants due to scale effects.
Keywords: R0; R4; F14; 330; geographical economics; manufacturing exports; domestic transport costs; South Africa; Industriegüteraußenhandel; Industriestandort; Transportkosten; Südafrika